EFFECTS OF FUNGI ON HUMAN SKIN (British Journal of Global Ecology and Sustainable Development, 2022)
Fungi - the world of eukaryotic organisms (bulimi). Living at the expense of ready-made organic substances, goiter is a heterotrophic organism. It usually has life in plants, soil, water, animals or in their hands. Depending on the method of release, it becomes parasitic and Saprophytic.